Climate and environmental history at Lake Levinson‐Lessing, Taymyr Peninsula, during the last 62 kyr. (18th October 2021) - Lenz, Matthias; Lenz, Marlene M.; Andreev, Andrei; Scheidt, Stephanie; Gromig, Raphael; Lebas, Elodie; Fedorov, Grigory; Krastel, Sebastian; Melles, Martin; Wagner, Bernd
ABSTRACT: The 45.95 m‐long sediment succession shown in core Co1401 from Lake Levinson‐Lessing allows the reconstruction of the largely unexplored environmental and climatic history of the Taymyr Peninsula of the past 62 kyr. The core was analysed with a multidisciplinary approach including lithological, granulometric, geochemical and pollen analyses. The proxy data indicate a relatively stable, herb‐dominated environment with only subtle changes between a cold/wet late Marine Isotope Stage (MIS) 4 and early MIS 3, mild/dry middle and late MIS 3 and a cold/dry MIS 2. The absence of pronounced climate fluctuations demonstrates that the Lake Levinson‐Lessing catchment was not covered by an ice sheet during this period. Changes in precipitation were likely caused by waxing and waning of the large Eurasian ice sheets outside of the Taymyr Peninsula, which changed the eastward moisture transport and atmospheric circulation patterns. MIS 1 at Lake Levinson‐Lessing was associated with overall warmer and wetter conditions and short‐term climate fluctuations during the Bølling–Allerød warming, Younger Dryas cooling and Preboreal transition, which indicates the influence of North Atlantic air masses.